A Solvent‐Exchange Strategy to Regulate Noncovalent Interactions for Strong and Antiswelling Hydrogels. Issue 52 (9th November 2020) - Xu, Liju; Gao, Shan; Guo, Qirui; Wang, Chen; Qiao, Yan; Qiu, Dong
Abstract: Physical hydrogels from existing polymers consisting of noncovalent interacting networks are highly desired due to their well‐controlled compositions and environmental friendliness; and therefore, applied as adhesives, artificial tissues, and soft machines. Nevertheless, these gels have suffered from weak mechanical strength and low water resistance. Current methodologies used to fabricate these hydrogels mainly involve the freezing–thawing process (cryogels), which are complicated in preparation and short in adjustment of polymer conformation. Here, taking the merits of noncovalent bonds in adjustability and reversibility, a solvent‐exchange strategy is developed to construct a class of exogels. Based on the exchange from a good solvent subsequently to a poor one, the intra‐ and interpolymer interactions are initially suppressed and then recovered, resulting in dissolving and cross‐linking to polymers, respectively. Key to this approach is the good solvent, which favors of a stretched polymer conformation to homogenize the network, forming cross‐linked hydrogel networks with remarkable stiffness, toughness, antiswelling properties, and thus underwater adhesive performance. The exogels highlight a facile but highly effective strategy of turning the solvent and consequently the noncovalent interactions to achieve the rational design of enhanced hydrogels and hydrogel‐based soft materials. Abstract : A solvent‐exchange strategy is developed to construct a class of stiff and antiswelling hydrogels (named as exogels). Key to this approach is the rational regulation of noncovalent interactions and thus the conformation of polymers and structure of the cross‐linked networks. Moreover, the unique sol–gel progression via solvent exchange makes exogels applicable for robust underwater adhesion.